2019
DOI: 10.46377/dilemas.v29i1.1880
|View full text |Cite
|
Sign up to set email alerts
|

Características de la actitud motivacional basada en el valor de los estudiantes hacia la educación física.

Abstract: El artículo explora las peculiaridades de la actitud motivadora basada en el valor de los jóvenes estudiantes modernos de Ucrania hacia las clases de educación física y el mantenimiento de un estilo de vida saludable. 501 estudiantes de tres instituciones de educación superior de Ucrania participaron en el estudio. La investigación fue realizada por los cuestionarios de los autores que permitieron estudiar la actitud de los estudiantes hacia la educación física tradicional, la salud física extracurricular y la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Decreased fluid stores in the body during exercise significantly reduces its subsequent loss of sweat during prolonged muscular activity. The studies [15][16][17][18] have shown a lack of tolerance to prolonged physical and thermal stress in the case of dehydration. For example, long-distance runners, slow down the running rate by almost 2% in the case of water loss by 1% of body weight due to dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased fluid stores in the body during exercise significantly reduces its subsequent loss of sweat during prolonged muscular activity. The studies [15][16][17][18] have shown a lack of tolerance to prolonged physical and thermal stress in the case of dehydration. For example, long-distance runners, slow down the running rate by almost 2% in the case of water loss by 1% of body weight due to dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…The modern model of the educational process defines a socially significant life strategy for the consistent formation of the health culture of students of pedagogical institutions of higher education i.e. future teachers as a necessary condition for the development of positive motivation of high schoolers and students for a healthy lifestyle [1][2][3]. Regular motor loads have a positive effect upon the level of a person's functional capabilities, increase emotional stability, reduce morbidity, ensure the acceleration of the warming-up process, contribute to the long-term preservation of the optimal pace, speed and efficiency of work movements [4][5][6].…”
Section: Introductionmentioning
confidence: 99%